Serum vitamin D, folic acid and B12 levels in wheezy children - Ture, Mehmet; Zeyrek, C. Dost; KOÇYİĞİT, ABDÜRRAHİM; KOÇYİĞİT, ABDÜRRAHİM (My University, 2013)
Objective: There are studies which determine the connection between deficiency or surplus of serum vitamin D, folic acid and B12, ashyma and wheezing attacks. This study aimed to determine whether or not there was any significant connection between serum vitamin D, folic acid and B12 levels and recurrent wheezing attacks.